SPRING TRITICALE GRAIN PRODUCTIVITY AND BIOENRGY EFFICINCY OF ITS GROWING DEPENDING UPON DIFFERENT SOWINGAND SOWING METHODS - Рожков, А. О. (Scientific Progress & Innovations, 2014)
The results of the three-year researches according to the coenotic factors influence: sowing methods and sowing rates on the grain productivity of spring triticale plants are given. The advantage of the striped sowing method on the increase of economic and bioenergy efficiency indices of spring triticale growing is established in the article. The crop capacity is higher while using the striped sowing method as well as economic and bioenergy efficiency indices of spring triticale growing are higher at a sowing rate of 550 seeds / m²; at the same time during the drill sowing method – at a sowing rate of 500 seeds / m².The established regularity is caused by weakening of coenotic tension in the striped sowing method which creates conditions for the full development of a larger number of plants per unit of the sown area.